2001
DOI: 10.1007/s002340100558
|View full text |Cite
|
Sign up to set email alerts
|

Magnetisation transfer measurements of the subcortical grey and white matter in Parkinson's disease with and without dementia and in progressive supranuclear palsy

Abstract: We measured the magnetisation transfer ratio (MTR) in the subcortical grey and white matter of 11 patients with idiopathic Parkinson's disease (PD) without dementia, six with PD with dementia (PDD), six with progressive supranuclear palsy (PSP), and 12 elderly control subjects to assess regional differences in structural brain damage. There were no significant differences in MTR in any region between PD and controls. However, patients with PDD had significantly lower MTR in the subcortical white matter, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…2732,63 These include diseases in the neurodegenerative spectrum, disorders of myelination and inflammation and mood and psychotic disorders. 26,28,29,3133,63 In these disorders, lower MTR has been demonstrated in neocortical, subcortical and limbic regions, and include gray and white matter architecture.…”
Section: Discussionmentioning
confidence: 99%
“…2732,63 These include diseases in the neurodegenerative spectrum, disorders of myelination and inflammation and mood and psychotic disorders. 26,28,29,3133,63 In these disorders, lower MTR has been demonstrated in neocortical, subcortical and limbic regions, and include gray and white matter architecture.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, no difference in MTR of the subcortical GM and WM has been found between patients with idiopathic PD and matched controls, whereas patients with PD and dementia had significantly lower MTR in the subcortical WM, including frontal WM and the genu of the corpus callosum, and those with progressive supranuclear palsy had significantly lower MTR in the subcortical GM, including the putamen, globus pallidus and thalamus. 152 In another study, lower MTR values in supratentorial WM and brainstem were found in PD patients without dementia, compared with controls. 153 Eckert et al 154 demonstrated changes in the MTR values in the globus pallidus, putamen, caudate nucleus, substantia nigra, and WM in idiopathic PD, in multiple system atrophy, and in progressive supranuclear palsy, matching the pathological features of the underlying disorder.…”
Section: Parkinson's Disease (Pd) and Allied Conditionsmentioning
confidence: 91%
“…By using MTI in patients with neurodegenerative parkinsonian disorders, abnormalities of the basal ganglia and substantia nigra were reported in patients with Parkinson's disease, MSA and PSP [60,61,62 ]. The most recent of these studies investigated the potential of MTI in the differential diagnosis of neurodegenerative parkinsonism including 37 patients with different parkinsonian syndromes and 20 age-matched controls [62 ].…”
Section: Magnetization Transfer Imagingmentioning
confidence: 97%